Study on tools and measuring results of wind speed using the agroclimate automatic weather station (AAWS) instrument at BMKG Sicincin - Astuti Kirana Fachry; Zulhendri Kamus; Sugeng Nugroho (Department of Physics – Universitas Negeri Padang UNP, 2017)
Wind speed and direction is required data in agriculture. Wind speed and direction will usually help pollinate plants, but it can also be used for the determination of the future grow. One of the instrument used to determine wind speed and direction are AAWS (Agroclimate Automated Weather Station). This instrument is used to measure weather elements Unsu-one speed and direction of this AAWS angin.Pada for measuring the weather elements such as wind speed and direction using an ultrasonic anemometer. The wind data must first be processed and analyzed so that it becomes useful information, one result is a diagram windrose plot (WRPLOT). WRPLOT can perform calculations in generating wind rose diagrams and frequency distribution of wind data quickly so that the information resulting from the analysis of wind speed and direction to be more informative and interactive. From the analysis of the measurement data of wind speed and direction were performed using WRPLOT showed, that the wind speed in the morning with a range 2,1-3,6m / s blowing from the southwest. During the day the wind speed decreased to 0.5 to 2.1 m / s blowing from the northeast and east. While at night the average wind speed was 0.5 to 2.1 m / s blowing from the northeast and east as well.